ОСОБЛИВОСТІ УПРАВЛІННЯ ТЕРИТОРІЯМИ ПІД ЧАС ВОЄННОГО СТАНУ В УКРАЇНІ - Vuychenko, Maryna (Zhytomyr Ivan Franko State University, 2024)
The article discusses the current problems of territory management in the conditions of the Russian-Ukrainian war, which has been going on for two years. A description of the real state of territorial communities is offered, their problems caused by the war are outlined. A cluster model of the distribution of territorial communities depending on the situation during the war is presented. Possible ways of solving the main problems arising in the management of territories during martial law are determined. The article emphasizes that Russia's war against Ukraine, which has been going on for two years, has become the sharpest and most dangerous test of Ukrainian society since independence. Virtually all state and public institutions and organizations, government and executive institutions underwent significant changes in form and content. This especially applies to territorial communities, which, despite their short existence, have actually become the centers of the reconstruction of Ukrainian civil society on the lines of martial law. Territorial communities shouldered the main burden of volunteer assistance to the Armed Forces of Ukraine and territorial defense, reception and accommodation of forced migrants, provision of humanitarian aid, educational, medical, legal, communal services, organization of business and employment, as well as mobilization work. The article notes that under the conditions of martial law, the forms and content of territory management activities, in particular municipal management bodies, have changed: military-civilian administrations have appeared in regions and former districts. During the two years of the war, the functions and boundaries of the administrative activities of local self-government bodies were agreed upon, taking into account the challenges that were caused by the full-scale aggression of Russia. The article notes that the burden of the war had the greatest impact on the stability and vitality of territorial communities. Despite the fact that today it is generally possible to positively evaluate the administrative-territorial reform that was carried out on the eve of the war, territorial communities are in unequal conditions of life, have different possibilities of functioning, and require management decisions that are adequate to the real situation. The article emphasizes that the primary task at the moment is to improve relations between the central government and local self-government bodies, taking into account the actual military, economic, demographic, social, political, and humanitarian situation. We are talking about a significant expansion of the powers of territorial communities in all spheres of social life. It is impossible to rule in wartime by peaceful methods. This is all the more important because the administrative and territorial reform depends on the results at the front.